Prevalence of Celiac Disease in Adult Patients with Iron Deficiency Anemia - Muhammad Aasim Khan, Habibullah Jan, Muhammad Omar Khan, Mohammad Hanif, Tariq Hassan, Liaqat Khurshid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Celiac disease is a gastrointestinal condition that is chronic and mediated by an immunological reaction to gluten present in different grains such as wheat, barley, and rye. Studies document that the incidence of celiac disease within the Pakistani population to be 29.3% and is highly prevalent among the younger age groups. Iron deficiency anemia is a major cause of anemia around the world, especially in developing countries such as Pakistan. Anemia has been acknowledged to be one of the major manifestations of celiac disease worldwide. This study will aim to assess the incidence and burden of celiac disease among the known anemic adult population of due to iron deficiency in tertiary care hospitals of Khyber Pakhtoonkhaw. Methodology: A cross-section study was conducted in the department of Gastroenterology Bacha Khan Medical Complex, Swabi and Northwest General Hospital & Research Centre Hayatabad, Peshawar during the period of six months from May 2021 to October 2021. Participants were recruited after assessment of criteria. All recruited participants were anemic and underwent extensive serological assessment for screening of celiac disease. For confirmation of celiac disease duodenal biopsies were performed at five different levels. Results: 5.4% of the participants (n= 108) were found to have positive results for screening of IgA tTG. 38% of these participants (n= 41) showed IgA tTG ranging between 20 – 79 who were found negative for IgA EMA. These participants were kept on a gluten-free diet for the following 6 months and were scheduled on a recall assessment after 6 months and then 1 year of diet. On follow up duodenal biopsies were performed for these participants and the outcomes were classified as Marsh 0. These participants comprising 38% of IgA tTG screening were discarded from the possible suspect of celiac disease.The remaining 62% (n= 67) population of positive IgA tTG screening test, comprising 3.35% of the entire recruited population had values for IgA tTG of greater than 100 and showed positive results in serology reports of IgA EMA. All 67 participants who tested positive underwent duodenal endoscopy on five sites for a definite diagnosis of celiac disease and were found to be celiac disease positive Conclusion: The study concludes that the prevalence of the celiac disease among the anemic population is high, and anemia can be considered an extra gastric manifestation of celiac disease. Majority of identified participants were female and shows a predilection for female susceptibility.